Dietary Trivalent Chromium Exposure Up-Regulates Lipid Metabolism in Coral Trout: The Evidence From Transcriptome Analysis - Wei, Lu; Li, Yu; Ye, Hengzhen; Xiao, Juan; Hogstrand, Christer; Green, Iain; Guo, Zhiqiang; Han, Dong (Frontiers in Physiology, 2021)
Diet quality greatly affects animal’s performance and metabolism. Despite trivalent chromium (Cr(III)) being considered as an essential element and its wide use in nutritional supplements for animals and humans, the potential toxicity of Cr(III) is unclear. The present study investigated the effects of organic Cr(III) (as chromium picolinate (CrPic)) on coral trout (Plectropomus leopardus). The fish were exposed to 200 mg kg-1 of dietary Cr(III) over 8 weeks and livers sampled for transcriptome analysis. There were 113 differentially expressed genes (DEGs) significantly enriched in CrPic group. Clusters of Orthologous Groups of proteins (COG) classified DEGs into 15 functional categories, with the predominant category related to lipid transport and metabolism (9.73%). Kyoto Encyclopedia of Genes and Genomes (KEGG) assigned DEGs into 6 major categories with robust DEGs part of lipid metabolism pathway (18.58%). Moreover, significantly up-regulated genes (dhcr7, dhcr24, ebp, lss, msmo1, sqle, cyp51, tm7sf2, sc5dl, fdft1, nsdhl, hsd17b7) were found for the steroid, terpenoid backbone and steroid hormone biosynthesis pathways. Our findings provided the first evidence that long-term high dose of Cr(III) intake caused lipid metabolism disorder and potential toxicity in fish. Cautious health risk assessment of dietary Cr(III) intake is therefore highly recommended for commercial and/or natural diets of aquatic animals, which has been largely ignored previously.